ChemInform Abstract: A New Route to Construct 1, 2‐Dihydroquinoxaline and 1, 4‐Benzoxazine Derivatives Stereoselectively and Its Application to Novel Pyrazolo[1, 5‐α]quinoxaline Oxides. Issue 25 (3rd June 2013) - Zhang, Dongxu; Yang, Yan; Gao, Meng; Shu, Wenming; Wu, Liuming; Zhu, Yanping; Wu, Anxin
Abstract Both 1, 4‐benzoxazines (III) and quinoxalines (VIII) are obtained stereoselectively via a novel approach from easily available 2‐methylthio‐1, 4‐enediones.